Synthesis and antibacterial activity of azo and aspirin-azo derivatives [Sintesis dan aktiviti antibakteria terhadap azo dan terbitan azo-aspirin] - Zainab, Ngaini; Ho, Boon Kui (Malaysian Society of Analytical Sciences, 2017)
A series of azo derivatives (1a-e) were synthesized via coupling reaction with of overall yield 58 - 72% while aspirin-azo derivatives (2a-e) were prepared by esterification reaction of aspirin and azo derivatives (1a-e) with overall yield 38 - 75%. In this study, the structures of synthesized compounds were characterized using elemental analysis (CHN), nuclear magnetic resonance (1H NMR and 13C NMR) and Fourier Transform Infrared (FTIR) spectroscopy. The synthesized compounds were tested on antibacterial activity against Escherichia coli ATCC 25922 and Staphylococcus aureus S48/81 via turbidimetric kinetic method. The azo derivative-substituted fluorine, 1d showed the highest antibacterial activities against Escherichia coli ATCC 25922 and Staphylococcus aureus S48/81 compared with other synthesized compounds. However, synthesized aspirin-azo derivatives (2a-e) showed weak antibacterial activity against tested bacteria due to bulky molecular structure thus hindered the penetration into bacterial cell wall. © 2017, Malaysian Society of Analytical Sciences.